2016
DOI: 10.20517/2394-5079.2016.09
|View full text |Cite
|
Sign up to set email alerts
|

Case report of the fourth laparoscopic liver resection and review of repeat laparoscopic resection for recurrent hepatocellular carcinoma in cirrhotic liver

Abstract: A 73-year-old woman with liver cirrhosis caused by hepatitis C virus (HCV) underwent treatment of three hepatocellular carcinomas (HCCs) in liver segment 4, following three previous laparoscopic liver resections (LLRs) over 73 months. Contrast-enhanced computed tomography showed three 0.5-1.2 cm HCCs deep within the portal territories of subsegments 4a and 4b. The patient underwent laparoscopic resection of 4a and 4b, with the preservation of the portal branch to 4c, after minimal adhesiolysis around segment 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…The study showed that LLR is beneficial for patients with Child-Pugh B cirrhosis compared to open procedures ( 22 , 23 ). Furthermore, LLR is speculated to have a benefit of less deterioration of liver function after surgery due to smaller damage related to surgical manipulation mentioned before ( 19 , 24 ), which can lead to long-term benefits during repeated treatment history in HCC/CLD patients.…”
Section: Perspectives Of Caudal Approach To Llrmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that LLR is beneficial for patients with Child-Pugh B cirrhosis compared to open procedures ( 22 , 23 ). Furthermore, LLR is speculated to have a benefit of less deterioration of liver function after surgery due to smaller damage related to surgical manipulation mentioned before ( 19 , 24 ), which can lead to long-term benefits during repeated treatment history in HCC/CLD patients.…”
Section: Perspectives Of Caudal Approach To Llrmentioning
confidence: 99%
“…Disorientation can easily occur owing to the lack of tactile sensation and the lack of an overview of the entire operative abdominal field. Simulation and navigation from pre- and intra-operative imaging studies and well-planned small anatomical resection to secure tumor localization in the resected area and the tumor-free resected margin are used to overcome this disadvantage ( 24 ).…”
Section: Perspectives Of Caudal Approach To Llrmentioning
confidence: 99%
“…The impact of alterations from the previous surgery on hepatic parenchyma and intrahepatic structure could be smaller in such cases. There were three repeat cases with anatomical resection or resections exposing major vessels (including S8 segmentectomy after 4-times LLR[ 40 ]) after previous anatomical resection who developed bile leakage and > 30 d hospital stay, among our 33 repeat and 12 three or more-time repeat LLR cases. Anatomical alterations surrounded by the scars and adhesions on major vessel structures could have big impacts on subsequent anatomical resection or resections exposing major vessels, experiences and evaluations of such setting of repeat LLR are required for the settlement (Table 2 ).…”
Section: Our Experiences and Future Perspectives Of Repeat Llrmentioning
confidence: 99%